Ragwort and nodding thistle control with novel 24d mixtures - James, T.K.; Rahman, A. (New Zealand Plant Protection, 2008)
For 50 years 24D has been the predominant chemical used for weed control on New Zealand farms but there is regulatory pressure to reduce application rates Pot and field experiments investigated the efficacy of lower rates of 24D when used in combination with either chlorsulfuron or mesotrione for control of ragwort (Senecio jacobaea) and nodding thistle (Carduus nutans) Experiments on potted plants evaluated herbicide combinations at several growth stages from small rosettes to prebolting while field trials were on weeds at bolting Ragwort was well controlled by the halfrate of 24D plus either chlorsulfuron or mesotrione For nodding thistle mesotrione was a better additive In the field trials control of both ragwort and nodding thistle from the half rate of 24D plus either chlorsulfuron or mesotrione was equal to or significantly better than that from the fullrate of 24D alone However in some instances there was also significant pasture damage